In Vivo F-Actin Filament Organization during Lymphocyte Transendothelial and Interstitial Migration Revealed by Intravital Microscopy - Yan, Serena L.S.; Hwang, Il-Young; Kamenyeva, Olena; Kehrl, John H. (iScience, 2019)
Actin is essential for many cellular processes including cell motility. Yet the organization of F-actin filaments during lymphocyte transendothelial migration (TEM) and interstitial migration have not been visualized. Here we report a high-resolution confocal intravital imaging technique with LifeAct-GFP bone marrow reconstituted mice, which allowed visualization of lymphocyte F-actin in vivo. We find that naive lymphocytes preferentially cross high endothelial venules (HEVs) using paracellular rather than the transcellular route. During both modes of transmigration F-actin levels rise at the lymphocyte leading edge as the cell engages the TEM site. Once the lymphocytes breach the endothelium, they briefly reside in HEV pockets before crossing into the parenchyma. During interstitial migration dynamic actin-based protrusions rapidly form and collapse to help drive motility. Using a panel of inhibitors, we established roles for actin regulators and myosin II in lymphocyte TEM. This study provides further insights into lymphocyte TEM and interstitial migration in vivo.